Deradikalisasi Penafsiran Al-Qur'an dalam Konteks Keindonesiaan yang Multikultur - Mustaqim, Abdul (Lajnah Pentashihan Mushaf Al-Qur'an, 2013)
It is recognized that in the Qur’an, there are verses that are textually have the potential to encourage violence acts. The idea of the importance of de-radicalization is related to the commentary of the Qur’anic verses that seem to be